{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

{Genetic Determinants of Electrocardiographic P-wave Duration and Relation to Atrial Fibrillation - Weng, L. C.; Hall, A. W.; Choi, S. H.; Jurgens, S. J.; Haessler, J.; Bihlmeyer, N. A.; Grarup, N.; Lin, H.; Teumer, A.; Li-Gao, R.; Yao, J.; Guo, X.; et al. (Circ Genom Precis Med, 2020)
Background - The P-wave duration (PWD) is an electrocardiographic (ECG) measurement that represents cardiac conduction in the atria. Shortened or prolonged PWD is associated with atrial fibrillation (AF). We used exome chip data to examine the associations between common and rare variants with PWD. Methods - Fifteen studies comprising 64,440 individuals (56,943 European, 5,681 African, 1,186 Hispanic, 630 Asian), and 230,000 variants were used to examine associations with maximum PWD across the 12-lead ECG. Meta-analyses summarized association results for common variants; gene-based burden and SKAT tests examined low-frequency variant-PWD associations. Additionally, we examined the associations between PWD loci and AF using previous AF GWAS. Results - We identified 21 common and low-frequency genetic loci (14 novel) associated with maximum PWD, including several AF loci (TTN, CAND2, SCN10A, PITX2, CAV1, SYNPO2L, SOX5, TBX5, MYH6, RPL3L). The top variants at known sarcomere genes (TTN, MYH6) were associated with longer PWD and increased AF risk. However, top variants at other loci (e.g., PITX2 and SCN10A) were associated with longer PWD but lower AF risk. Conclusions - Our results highlight multiple novel genetic loci associated with PWD, and underscore the shared mechanisms of atrial conduction and AF. Prolonged PWD may be an endophenotype for several different genetic mechanisms of AF.

{Association between ABO haplotypes and the risk of venous thrombosis: impact on disease risk estimation - Goumidi, L.; Thibord, F.; Wiggins, K. L.; Li-Gao, R.; Brown, M. R.; van Hylckama Vlieg, A.; Souto, J. C.; Soria, J. M.; Ibrahim-Kosta, M.; Saut, N.; Daian, D.; Olaso, R.; et al. (Blood, 2021)
10.1182/blood.2020008997Genetic risk score (GRS) analysis is a popular approach to derive individual risk prediction models for complex diseases. In venous thrombosis (VT), such type of analysis shall integrate information at the ABO blood group locus, which is one of the major susceptibility loci. However, there is no consensus about which single nucleotide polymorphisms (SNPs) must be investigated when properly assessing association between ABO locus and VT risk. Using comprehensive haplotype analyses of ABO blood group tagging SNPs in 5425 cases and 8445 controls from 6 studies, we demonstrate that using only rs8176719 (tagging O1) to correctly assess the impact of ABO locus on VT risk is suboptimal, because 5% of rs8176719-delG carriers do not have an increased risk of developing VT. Instead, we recommend the use of 4 SNPs, rs2519093 (tagging A1), rs1053878 (A2), rs8176743 (B), and rs41302905 (O2), when assessing the impact of ABO locus on VT risk to avoid any risk misestimation. Compared with the O1 haplotype, the A2 haplotype is associated with a modest increase in VT risk (odds ratio, ∼1.2), the A1 and B haplotypes are associated with an ∼1.8-fold increased risk, whereas the O2 haplotype tends to be slightly protective (odds ratio, ∼0.80). In addition, although the A1 and B blood groups are associated with increased von Willebrand factor and factor VIII plasma levels, only the A1 blood group is associated with ICAM levels, but in an opposite direction, leaving additional avenues to be explored to fully understand the spectrum of biological effects mediated by ABO locus on cardiovascular traits.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

{Rare and low-frequency exonic variants and gene-by-smoking interactions in pulmonary function - Yang, T.; Jackson, V. E.; Smith, A. V.; Chen, H.; Bartz, T. M.; Sitlani, C. M.; Psaty, B. M.; Gharib, S. A.; O'Connor, G. T.; Dupuis, J.; Xu, J.; Lohman, K.; et al. (Sci Rep, 2021)
. This study investigates the utility of assessing gene-by-smoking interactions and underscores their effects on potential pulmonary function.

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.